INCREASING STUDENTS LEARNING OUTCOMES IN CLASS IV ON SCIENCE CONTENT THROUGH POWERPOINT MEDIA - Muhammad Fardilah Husain; Agung Setyawan (Citra Dharma Cindekia, 2022)
One of the interesting learning media that can be searched and operated easily included in the science content is powerpoint media. Therefore, this study aims to improve student learning outcomes on science content through powerpoint learning media on class IV MI Bani Hasyim Lengkong Cerme Gresik material. This type of research is Classroom Action Research using a research design from Kemmis and Tagart which consists of two cycles with each cycle consisting of one lesson. The subjects of this study were students of class IV MI Bani Hasyim Lengkong Cerme Gresik, totaling 18 students consisting of 10 male students and 8 female students. The data collection techniques used were observation, structured interviews, tests (pre-test and post-test), and documentation. The data analysis technique used is an interactive model. The results of the Classroom Action Research showed that there was an increase in the actions of cycle I and cycle II. Fourth grade students' learning outcomes have increased in science content after using powerpoint learning media. This is indicated by an increase in the percentage of complete learning outcomes and the average learning outcomes of fourth grade students at MI Bani Hasyim Lengkong Cerme Gresik.